(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The lexical-semantic deployment of the temporal nomination «spring» in the dictionary of Ukrainian poetry of the second half of the twentieth century is observed in this article. The peculiarities of imaginative and esthetic and expressive development of this nomination are analyzed. Semantic-associative potential of the distributive «spring» in the language style of the Ukrainian authors of the second half of the twentieth century is found.